Legal Protection for Creditors Who Recipient of Motor Vehicle Fiduciaries After Constitutional Court Decision Number 18/PUU-XVII/2019 & Number 2/PUU-XIX/2021 (Study at BRI Finance Malang Branch) - Ahmad Shoifi; Djumikasih, Djumikasih; Laila, Fathul (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Fiduciary is a material guarantee which is a development of other material guarantees, namely Pawning. This development is a living need in society because pawning collateral which requires control of the pledged collateral object by the creditor is felt to be less supportive of business because the debtor cannot benefit from the collateral object so material collateral is needed which is more beneficial for the debtor but also the creditor's interests can still be protected. Execution of fiduciary guarantees can be carried out in accordance with article 29 UUJF, namely if the debtor or fiduciary person breaks his promise, the execution of the object that is the object of fiduciary guarantee point 1 above is the priority given by the material guarantee institution which is referred to as Parate execution, which is regulated in Article 15 paragraph (3) of the Fiduciary Guarantee Law (hereinafter abbreviated to "UUJF") which states that "If the debtor breaks his promise, the fiduciary recipient has the right to sell the object that is the object of the fiduciary guarantee under his own authority." The research method used is the Socio Legal Research Method or commonly used as empirical juridical research. Empirical legal research, namely data obtained directly from the community as the first source through field research. The research location is at the BRI Finance Malang Branch Office which is one of BRI's subsidiary entities which operates in the financing sector located in Malang City. One of the financing products from BRI Finance is Multipurpose Motor Vehicle Ownership Credit where the collateral is a motor vehicle tied to the institution fiduciary material guarantee. The results of the research show that the execution of credit collateral in the form of a motor vehicle tied to a fiduciary with the Constitutional Court decision Number 18/PUU/XVII/2019 which is confirmed by the Constitutional Court decision No.2/PUU-XIX/2021 becomes weaker because the creditor's preference rights are limited. The institution granted fiduciary material guarantees in the form of an execution parate cannot be carried out unilaterally because it must obtain the debtor's approval regarding the element of breach of contract/default and also the voluntary handover of fiduciary objects